THE IMPORTANCE OF DEVELOPING PRIMARY STUDENTS' INTEREST IN LEARNING AND SKILLS - Yaxshiboyeva Nargiza Rustamqulovna (Bright Mind Publishing, 2025)
This article discusses the development of interest in learning and skills of primary school students. Introduction, Formation of interest in learning in students, Development of learning skills, Use of innovative and modern methods, Parent-teacher cooperation, Taking into account the personal approach of students, Scientific point of view and practical examples, Practical examples, Statistical data, The role of modern approaches, Pedagogical recommendations, Conclusion, List of references.
Keywords: Primary education, arousing interest in students, learning skills, interactive methods, innovative approaches, person-centered education, parent-teacher cooperation, lesson effectiveness.